2016
DOI: 10.5194/aab-59-477-2016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and distance of Iranian goat breeds (Markhoz, Mahabadi and Lori) compared to the Beetal breed using inter-simple sequence repeat (ISSR) markers

Abstract: Abstract. The aim of this study was to investigate the genetic diversity and structure in three Iranian native goat breeds (Markhoz, Mahabadi and Lori) and the Beetal imported breed using inter-simple sequence repeat (ISSR) markers and also to investigate ISSR markers' potential in order to genetically separate single (S) and twin-birth (T) subpopulations. Blood samples were collected from 210 animals for this purpose. In total, 16 primers were used, and finally 5 primers were selected based on the number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Moreover, the LS phenotypic and environmental averages had considerable decreases in recent years (Figure 1), which could decrease the estimate of h 2 , as the result of an increase in phenotypic and environmental variances. Low heritability of LS in the present study supports previous concepts about the need of more studies on major genes, and finding genetic background of LS trait in different goat breeds (Simaei-Soltani et al, 2016). Low estimates were also obtained for repeatability and permanent environment coefficient; thus the LS repeatability is entirely due to permanent environmental effects.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the LS phenotypic and environmental averages had considerable decreases in recent years (Figure 1), which could decrease the estimate of h 2 , as the result of an increase in phenotypic and environmental variances. Low heritability of LS in the present study supports previous concepts about the need of more studies on major genes, and finding genetic background of LS trait in different goat breeds (Simaei-Soltani et al, 2016). Low estimates were also obtained for repeatability and permanent environment coefficient; thus the LS repeatability is entirely due to permanent environmental effects.…”
Section: Discussionsupporting
confidence: 89%
“…Previous DNA genotyping studies revealed moderate genetic diversity in Markhoz goat (Simaei-Soltani et al 2016). Shokrollahi (2015), Khani et al (2015), and Shokrollahi & Morammazi (2018) reported a very little genetic variation among the Markhoz goat.…”
Section: Discussionmentioning
confidence: 95%
“…Previous DNA genotyping studies revealed moderate genetic diversity in Markhoz goat (Simaei‐Soltani et al . ). Shokrollahi (), Khani et al .…”
Section: Discussionmentioning
confidence: 97%
“…Ten specific ISSR primers (table 1) were used. PCR amplification protocol was carried out according to Simaei-Soltani et al, (2016) with some minor modifications. Polymerase chain reaction was performed in a 15 µL final volume containing 1 unit Taq DNA polymerase, 1.5 µL of 10× PCR buffer, 0.2 mM dNTPs, 0.25 µM of primer, 25 mM of MgCl2 and 50-100 ng of genomic DNA.…”
Section: Inter-simple Sequence Repeat (Issr) Amplificationmentioning
confidence: 99%